The Qur'an and Riba - Sayyid, Tahir (Markazi Anjuman Khuddam-ul-Qur'an, Lahore (Pakistan), 1996)
This article is a chronological study of the Ayat on riba. It explains the legislative process on riba in the light of the Ayat on riba that were revealed on five occasions: 5 years before the Hijrah (Surah ar-Room, 30: 39), shortly after the Hijrah (Surah an-Nisaa', 4: 160-162), Shawwal 3AH (Surah Aale 'Imran, 3: 130-136), late 3AH or early 4AH (Surah al-Baqarah 2: 275-277) and sometime in late 9AH or 10AH before Hajjat-ul-Wida'. Backgrounds of the said Revealations the linkages between them are also explained.